A Closer Look at the Notorious Birthday Coincidences. (24th October 2013) - Falk, Ruma
Summary The article asks about the minimal number of persons required for achieving a probability 1/2 that a. At least two share a birthday, b. At least one shares the reader's birthday. A basic question about the necessary number of checks underlies both problems.